PENGARUH STRATEGI PERUSAHAAN TERHADAP PENINGKATAN DISTRIBUSI KORAN PT. PIKIRAN RAKYAT - Fitriana Dewi Sumaryana; Kristianty Retnawati; Siti Aisah Isvianti (Jurnal Co Management, 2019)
This present study is intended to identify the impact of corporate stategy over newspaper distribution at PT.Pikiran Rakyat. Along with increasing of Competition in mass business, the company must make the right strategy to distribute their products. The quality of products and services of print media will determine whether the company is able to compete in the global market or not. The simple requirement that must be fulfilled by the company is the company's ability to provide products and services according to the needs and desires of the community. Distribution factors are important for conveying company products to consumers. This study was designed as a quantitative study, so that the data is analyzed to determine the relationship between company strategy and distribution of newspapers to employees of PT. Pikiran Rakyat. Data and information obtained are related to the company's strategy towards increasing the distribution of PT Pikiran Rakyat newspaper. Data retrieval instruments using questionnaires or questionnaires and direct observations which are then analyzed using SPSS. The retsult of data analysis showed that the company's strategy influencing the process of distributing newspapers at PT. Pikiran Rakyat.